2008
DOI: 10.1016/j.cell.2008.01.043
|View full text |Cite
|
Sign up to set email alerts
|

PILRα Is a Herpes Simplex Virus-1 Entry Coreceptor That Associates with Glycoprotein B

Abstract: Glycoprotein B (gB) is one of the essential components for infection by herpes simplex virus-1 (HSV-1). Although several cellular receptors that associate with glycoprotein D (gD), such as herpes virus entry mediator (HVEM) and Nectin-1, have been identified, specific molecules that mediate HSV-1 infection by associating with gB have not been elucidated. Here, we found that paired immunoglobulin-like type 2 receptor (PILR) alpha associates with gB, and cells transduced with PILRalpha become susceptible to HSV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
309
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(316 citation statements)
references
References 36 publications
7
309
0
Order By: Relevance
“…With respect to gB, the crystal structure shows a trimer with a central coiled-coil and an overall structure similar to that of the fusion glycoprotein G of vesicular stomatitis virus in its postfusion conformation (21,22). Recently, a receptor for gB was described (23). Of note, although for virus-to-cell entry and for cell-cell fusion, fusion requires the simultaneous presence of gB and gH/gL, fusion of perinuclear virions with the outer nuclear membranes appears to necessitate either gH/gL or gB (24).…”
Section: Herpes Simplex Virus (Hsv)mentioning
confidence: 99%
“…With respect to gB, the crystal structure shows a trimer with a central coiled-coil and an overall structure similar to that of the fusion glycoprotein G of vesicular stomatitis virus in its postfusion conformation (21,22). Recently, a receptor for gB was described (23). Of note, although for virus-to-cell entry and for cell-cell fusion, fusion requires the simultaneous presence of gB and gH/gL, fusion of perinuclear virions with the outer nuclear membranes appears to necessitate either gH/gL or gB (24).…”
Section: Herpes Simplex Virus (Hsv)mentioning
confidence: 99%
“…[129][130][131] Several host surface receptors have been identified, including herpes virus entry mediator, nectin-1, 3-O-sulphated heparan sulphate and paired immunoglobulin-like type 2 receptor α (PILR-α). [132][133][134][135] However, a study by Shukla et al 136 identified nectin-1 as being the crucial mediator in a murine model of corneal infection. Of note when considering the mechanism of HSV1 infection is the fact that phylogenetic analysis suggests the evolution of at least six distinct HSV1 genogroups, with multiple recombination events detected in the genome coding for glycoproteins.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
“…HSV belonging to the family of alpha-herpes viruses, typical pathogens responsible for mucosal lesions of the mouth and genital organs in humans, binds and enters host cells by a complex process involving the essential viral glycoproteins B (gB), gD, gH, and gL and multiple cellular molecules including the tumor necrosis factor receptor (TNFR) family [123], nectin-1 or nectin-2 (two members of the immunoglobulin superfamily) [124], paired immunoglobulin-like type 2 receptor (PILR) [125], and particular type of modified HSPGs [126,127]. Raft associations of TNFR are essential for TNFalpha-mediated NF-B activation [128].…”
Section: Role Of Membrane Rafts In Virus Entrymentioning
confidence: 99%